2000
DOI: 10.1051/aas:2000278
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the H2O maser associated with U Orionis

Abstract: Abstract. H 2 O line observations at λ = 1.35 cm of the Mira Ceti-type variable star U Ori are reported. The observations cover the time interval from March, 1980, to September, 1999. Variations of the integral flux and velocity centroid of the H 2 O line are analysed. The flux in general correlates with the visual light curve, following it with some phase delay ∆ϕ ∼ 0.2 − 0.4P (P is the period of the star). The maser emission is generated in a quasistationary layer of gas and dust at a distance of about 10 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Lekht et al (2005) detected slightly less flux than we did for S Per in 1994, and more in 1999. Rudnitskij et al (2000) show that we detected a similar amount of maser emission from U Ori as they did in 1994 and 1999. The single-dish flux of RT Vir within a few months of our observations (Mendoza-Torres et al 1997;Lekht et al 1999) was lower than the closest interferometry measurements, but both sets of observations show that it is highly variable, changing flux density by a factor of 2 in a few months.…”
Section: Observationssupporting
confidence: 84%
See 1 more Smart Citation
“…Lekht et al (2005) detected slightly less flux than we did for S Per in 1994, and more in 1999. Rudnitskij et al (2000) show that we detected a similar amount of maser emission from U Ori as they did in 1994 and 1999. The single-dish flux of RT Vir within a few months of our observations (Mendoza-Torres et al 1997;Lekht et al 1999) was lower than the closest interferometry measurements, but both sets of observations show that it is highly variable, changing flux density by a factor of 2 in a few months.…”
Section: Observationssupporting
confidence: 84%
“…Stronger shocks are likely to propagate out from the stellar surfaces of U Ori and U Her, which could flatten maser clouds. Rudnitskij et al (2000) describes signs of the impact of stellar pulsations apparent from long-term spectral monitoring of H 2 O masers around U Ori. Moreover, both U Ori and U Her have undergone OH maser flares likely to have originated in the inner CSE (Pataki & Kolena 1974;Chapman & Cohen 1985;Etoka & Le Squeren 1997).…”
Section: Matter-bounded Masersmentioning
confidence: 99%
“…Four epochs of MERLIN observations from 1994-2001 show that the water masers always fall within a hollow shell bounded by radii of ∼ 8 and ∼ 35 AU, wherein the brightest emission is always at a similar distance from the star, although at different position angles. The weighted mean velocity of the brightest masers has drifted by less than 1 km s −1 in 20 yr [113]. Unusually, the apparent size of individual bright maser components is not inversely proportional to the brightness temperature as expected for beaming from approximately spherical clouds, but increases, as shown in Fig.…”
Section: Pos(8thevn)042mentioning
confidence: 63%
“…According to our data of March and June 1980, this star was 'silent' in H 2 O with the peak flux density below 10-12 Jy. However, between June and October 1980 the U Ori maser brightened to more than 1000 Jy (Berulis et al 1983;Rudnitskij et al 2000). Similar events took place in the H 2 O maser associated with the Mira-like semiregular variable W Hya in 1981 (Berulis et al 1983) and in 2001.…”
Section: Observationsmentioning
confidence: 82%
“…This may be due to a periastron shock wave episode of a planet in a highly eccentric orbit with a period P ∼ 15 years. Some other stars (e.g., U Ori, Rudnitskij et al 2000) have already shown some hints of H 2 O maser 'superperiodicity'of 12-15 years, which could be associated with planetary revolution periods.…”
Section: Effects Of a Relic Planetary System Around A Red Giantmentioning
confidence: 99%